Chemical Kinetic and Mechanistic Approach of Cinacalcet Hydrochloride by Sodium N-Chloro Benzene Sulfonamide in Acid Medium - Kallesha, N.; Prasad, Ningegowda; Shivakumara, N.; Narasimhamurthy, K. H. (Progress in Chemical Science Research Vol. 9, 2023)
Cinacalcet Hydrochloride is a United States of Food and Drug Administration (USFDA) approved Drug, marketed under the trade name Mimpara, used for the treatment of secondary hyperparathyroidism. The aim of the current investigation was Kinetic and mechanistic study of Cinacalcet Hydrochloride by sodium-N-chloro-benzene sulfonamide or chloramine-B (CAB) in HCl medium was studied at 308 K. The reaction follows first order dependence on [CAT]0 and [substrate]0, fractional order dependence on [HCl] ion. Variation of ionic strength and addition of benzene sulfonamide have no significant effect on the rate. The reaction was studied at five different temperatures; however, the thermodynamic parameters have been assessed from the Arrhenius plots. The stoichiometry of the reaction has been established to be 1:2 and oxidation product Imine was predicted by Chromatographic and Spectroscopic analysis. The observed results were supported by probable mechanism and the related rate law has been deduced.